Diglossic code-switching phenomenon in Jordanian newspaper satirical articles - Algweirien, Hussien; Al-Quran, Majed; Al-Khawaldeh, Nisreen (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the functions that the diglossic code-switching between Modern Standard Arabic and Jordanian Arabic serves in Jordanian newspaper ironic articles. It also explores Jordanians’ attitudes towards this linguistic phenomenon. Data were collected through mixed methods; a content analysis of numerous diglossic code-switched expressions in the target articles, an interview with a Jordanian satirist and a questionnaire distributed to 140 Jordanians. The qualitative analysis of the diglossic code-switched expressions and the interview revealed that diglossic code-switching serves specific sociolinguistic functions including an implicit criticism of crucial political, economic and social issues, presenting distinctive sociocultural features, expressing national identity as well as insulting and cursing. The diglossic switched expressions appear as key linguistic elements full of social and cultural distinctiveness. They are found powerful, purposeful and creative tools for conveying specific ironic messages that may not be efficiently communicated through MSA only. Diglossic code-switching also fulfills certain discourse functions encompassing quotation, clarification and elaboration, reiteration for emphasis, inserting parenthetical comments and interjection. The interviewees reveal positive attitudes towards this linguistic phenomenon except with the idea that it may pose a long-term negative threat to the mother tongue. The results demonstrate that written diglossic-code switching constitutes part of the linguistic variation in Jordan and is a good technique for attaining linguistic accommodation with the audience as it increases simplicity and clarification and decreases the language barrier with readership. The study concludes with some theoretical and pedagogical implications and recommendations for further promising research.